Strategic Priorities of Shipbuilding of a Fishery Complex of Russia - Andrey Alfredovich Beletskiy (Управленческое консультирование)
In the article tendencies of a condition of fleet of a fishery complex during the Post-Soviet period are considered and prerequisites for formation of measures of the state support of development of branch are analyzed. The special attention is paid to forecasting of variation consequences of implementation of the current offers on modification of the legislation on fishery. The author offers own vision of measures of state regulation for development of a fishing complex of Russia in general and investment appeal of updating and modernization of fleet in particular.